Integration Through Separation – The Role of Lateral Membrane Segregation in Nutrient Uptake - Busto, Jon V.; Wedlich-Söldner, Roland (Frontiers in Cell and Developmental Biology, 2019)
Nutrient transporters are prominent and ubiquitous components of the plasma membrane in all cell types. Their expression and regulation is tightly linked to the cells’ needs. Environmental factors such as nutrient starvation or osmotic stress prompt an acute remodeling of transporters and the plasma membrane to efficiently maintain homeostasis in cell metabolism. Lateral confinement of nutrient transporters through dynamic segregation within the plasma membrane has recently emerged as an important phenomenon that facilitates spatio-temporal control of nutrient uptake and metabolic regulation. Here we review recent studies highlighting the mechanisms connecting the function of amino acid permeases with their endocytic turnover and lateral segregation within the plasma membrane. These findings indicate that actively controlled lateral compartmentalization of plasma membrane components constitutes an important level of regulation during acute cellular adaptations.